2020
DOI: 10.3390/nano10112110
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Optical Properties of Self-Catalyzed Axially Heterostructured GaPN/GaP Nanowires Embedded into a Flexible Silicone Membrane

Abstract: Controlled growth of heterostructured nanowires and mechanisms of their formation have been actively studied during the last decades due to perspectives of their implementation. Here, we report on the self-catalyzed growth of axially heterostructured GaPN/GaP nanowires on Si(111) by plasma-assisted molecular beam epitaxy. Nanowire composition and structural properties were examined by means of Raman microspectroscopy and transmission electron microscopy. To study the optical properties of the synthesized nanoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 78 publications
2
12
0
Order By: Relevance
“…Finally, NW growth was interrupted by closing both Ga and P 2 shutters and subsequent sample cooling. An in situ analysis of the NW crystal structure performed with reflection high energy electron diffraction (RHEED) patterns demonstrated that the described growth conditions yielded stable formation of GaP NWs with a zinc-blende structure as it was previously reported in [36][37][38].…”
Section: Gapas/gap Nw Led Array Synthesissupporting
confidence: 62%
“…Finally, NW growth was interrupted by closing both Ga and P 2 shutters and subsequent sample cooling. An in situ analysis of the NW crystal structure performed with reflection high energy electron diffraction (RHEED) patterns demonstrated that the described growth conditions yielded stable formation of GaP NWs with a zinc-blende structure as it was previously reported in [36][37][38].…”
Section: Gapas/gap Nw Led Array Synthesissupporting
confidence: 62%
“…According to planar GaP growth, we established the stoichiometric V/III flux ratio of 6. In all of the growth runs, at the first stage P 2 BEP was set at 8.4 × 10 −7 Torr (V/III ratio of 12) to obtain stable self-catalytic VLS NW formation reported previously [ 4 , 39 ]. At the second stage, P 2 flux was increased up to 1.26 × 10 −6 Torr (V/III ratio of 18) to promote gradual catalytic droplet consumption, which seems the most prominent way to control the catalyst droplet shape and thus the nucleation of the WZ phase [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Typical cross-section SEM-images of the synthesized samples are presented in Figure 1 b–d. One can note that vertical VLS NWs growth occurs simultaneously with the unwanted three-dimensional islands formed via vapor-solid (VS) mechanism [ 39 , 41 ]. Parasitic 3D islands are depicted with magenta polygons in Figure 1 and possess irregular shapes which can be associated with a large number of structural defects, as will be shown further in the XRD section.…”
Section: Resultsmentioning
confidence: 99%
“…To summarize, the current work has revealed the key role of the design of ligands and PMCs in terms of the broad variation of mechanical and SH properties and provides a route to produce a variety of cobalt-incorporated SH materials exhibiting useful elastic properties. The obtained cobalt­(II)-incorporating polysiloxanes, particularly Co-Bipy-PDMSs, are promising polymers for the fabrication of highly elastic SH membranes, e.g., for optoelectronic devices, , and as coatings for electrokinetic separations and electrostatic discharge materials. , …”
Section: Discussionmentioning
confidence: 99%